COMPARISON OF NORDIC WALKING AND SENAM LANSIA ON FUNCTIONAL CAPACITY IN POSTMENOPAUSAL WOMEN - Hakim, Hernanda Haudzan; Julianti, Hari Peni; Dewi, Novita Sari (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: Functional capacity is the ability to perform physical activities without pain or fatigue. In postmenopausal women, there are significant changes in cardiovascular, musculoskeletal, and pulmonary functions, which can lead to a decrease in functional capacity. Regular and controlled physical activity can enhance muscle metabolism and cardiopulmonary fitness, thereby increasing functional capacity. Nordic walking and senam lansia are examples of popular physical activities in the Indonesian community, particularly among postmenopausal women. Objective: To compare the effect of Nordic walking and senam lansia on functional capacity of postmenopausal women. Methods: This study was a quasi experimental pretest-posttest control group design. There were 26 participants divided into two groups: group A (n=13) received Nordic walking training 3 times a week for 12 weeks, and group B (n = 13) received senam lansia 3 times a week for 12 weeks.  Functional capacity is obtained through the measurement of METs scores, converted from the result of 6-minute walking test (6MWT) using the Nury formula. Results: After twelve weeks, there was a significant improvement in METs scores in both the Nordic walking group (p=0.001) and the senam lansia group (p<0.001). There was a statistically significant difference in delta METs score between the Nordic walking group (0.98±0.12) and the senam lansia group (0.40±0.24) (p<0.001). Conclusion: Both Nordic walking and senam lansia improved functional capacity in postmenopausal women after 12 weeks, with Nordic walking producing a greater effect.